Pengaruh Pendidikan, Pengangguran dan Kepadatan Penduduk Terhadap Kriminalitas di Indonesia - Eveline Hachica; Mike Triani (Universitas Negeri Padang, 2022)
This study aims to determine the effect of several variables on crime in Indonesia. The variables used in this research are Education, Unemployment, and Population Density. This study uses secondary data with panel data using 31 provinces in Indonesia with the Random Effect Model (REM) approach.The results showed that: (1) Education had a negative and insignificant effect on crime (2) Unemployment had a positive and insignificant effect on crime (3) population density had a positive and significant effect on crime.The results of this study are expected to the government and the authorities to be active in conducting socialization aimed at creating security and based in areas prone to crime and implementing education improvement programs and creating jobs to improve the community's economy.